2023
DOI: 10.1097/j.jcrs.0000000000001265
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes after bilateral refractive lens exchange with a continuous-range-of-vision intraocular lens

Abstract: Purpose: Clinical evaluation of a diffractive continuous-range-of-vision IOL that combines bifocal and extended depth of focus technologies in refractive lens exchange patients. Setting: University Eye Clinic Design: Prospective interventional clinical study. Methods: Bilateral implantation of the TECNIS Synergy IOL (Johnson & Johnson Surgical Vision, Irvine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In this study, we compared both and showed that Symfony ® and Synergy ® had similar values, with a higher value at each point in Symfony ® without any significance. Khoramnia et al [32] reported exact mesopic CS values for Symfony ® , which were 1.56 ± 0.20, 1.44 ± 0.25, 0.92 ± 0.38, and 0.44 ± 0.37 at illumination levels of 3.0, 6.0, 12.0, and 18.0, respectively, and were similar to our results. iTrace measures the objective optical quality of an IOL using a retinal image obtained from a ray-tracing aberrometer system [33].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we compared both and showed that Symfony ® and Synergy ® had similar values, with a higher value at each point in Symfony ® without any significance. Khoramnia et al [32] reported exact mesopic CS values for Symfony ® , which were 1.56 ± 0.20, 1.44 ± 0.25, 0.92 ± 0.38, and 0.44 ± 0.37 at illumination levels of 3.0, 6.0, 12.0, and 18.0, respectively, and were similar to our results. iTrace measures the objective optical quality of an IOL using a retinal image obtained from a ray-tracing aberrometer system [33].…”
Section: Discussionsupporting
confidence: 91%
“…4–6 Several studies have confirmed the capability of this type of implant to provide an effective restoration of the visual function at different distances, with optimal visual quality at even closer than 40 cm. 7–15 Indeed, a trend to obtain a wider range of functional focus with this hybrid IOL was observed in a comparative study of this IOL with other 2 trifocal IOLs. 16 However, to this date, there is no report showing if these results are also achieved with the toric version of this hybrid IOL, Tecnis Synergy Toric II, which is implanted in eyes with preexisting corneal astigmatism.…”
mentioning
confidence: 68%
“…6 By contrast, Khoramnia et al found in another sample of 28 patients implanted with the same IOL a mean postoperative monocular DCIVA measured at 80 cm, UNVA measured at 40 cm, and DCNVA measured at 40 cm of −0.03 ± 0.09 logMAR, 0.03 ± 0.09 logMAR, and −0.01 ± 0.06 logMAR, respectively. 9 Despite these differences among studies that may be attributed to different procedural aspects, the visual outcomes were always within acceptable values. Indeed, in our series, a total of 100%, 81.8%, and 90.9% achieved postoperative CDVA, DCIVA measured at 80 cm, and DCNVA measured at 40 cm of 20/30 or better, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations